Active Learning by Visual Programming: Pedagogical Perspectives of Instructivist and Constructivist Code Teachers and Their Implications on Actual Teaching Strategies and Students' Programming Artifacts. (March 2022) - Kesler, Avital; Shamir-Inbal, Tamar; Blau, Ina
The integration of visual programming in early formal education has been found to promote computational thinking of students. Teachers' intuitive perspectives about optimal learning processes – "folk psychology" – impact their perspectives about teaching "folk pedagogy" and play a significant role in integrating educational technologies, such as visual programming, within the formal curriculum. This study was conducted based on the mixed method research paradigm. First, a folk pedagogy questionnaire was distributed to 89 teachers who integrate differing technologies in their classroom in order to identify the teachers' pedagogical perspectives: constructivist versus instructivist. Then, semi-structured interviews were conducted with 24 teachers who teach Scratch in order to gain a deeper understanding of their instructivist/constructivist perspectives and actual pedagogical practices and strategies. Finally, we analyzed 96 students' programming artifacts to explore differences, if any, in students' outcomes related to the pedagogical perspectives of their teachers. Findings revealed that pedagogical perspectives are reflected in teaching strategies and assessment practices employed in a visual programming environment. It is promising that teaching visual programming promoted constructivist pedagogy even among instructivist teachers and was consequently reflected in student perspectives and expressed in their programming artifacts. We discuss theoretical and educational implications of these findings.